The Gamma-G Family: Brief Survey and COVID-19 Application - Gauss M. Cordeiro; Alexsandro A. Ferreira (Stats)
In recent years, the gamma-G family has gained significant popularity for generating new distributions by incorporating an additional shape parameter into the baseline model. This article compiles and documents the existing gamma-G distributions and demonstrates their application to real COVID-19 data.